PENERAPAN METODE DEMPSTER SHAFER UNTUK DIAGNOSA KERUSAKAN BANGUNAN AKIBAT GEMPA DI KOTA JAYAPURA - Limbong, Alfa Natasya; Limbong, Josua Josen Alexander; Nurhayati, Siti; Tonggiroh, Mursalim (Universitas Multi Data Palembang, 2024)
One of the impacts of the earthquake that hit Jayapura City in early 2023 was damage to buildings (houses and buildings). The ineffectiveness of the process of inventorying and identifying building damage is one of the obstacles faced by the Jayapura City BPBD, due to the limited number of personnel, the wide coverage of the painting area, and the inventory and discovery processes that are still being carried out manually. In addition, community knowledge about building damage and post-earthquake handling solutions is still limited. For this reason, an expert system is needed as a tool to carry out an inventory and help the level of damage to buildings along with recommendations for solving them quickly and precisely. This study aims to apply the Dempster Shafer method to diagnose earthquake damage to buildings. This method is a case approach technique used to measure a possibility that occurs based on a cause. For problem assistance using the Fishbone analysis method, system design using the Unifield Modeling Language (UML), and for testing using Black-Box Testing. The results of research using the Dempster Shafer method recommend three categories of building damage levels, namely light damage, moderate damage, and heavy damage. This study also recommends solutions for handling according to the type and level of damage to buildings experienced, so that the results of the inventory and damage assistance can be faster and more precise, and the community can be more vigilant in anticipating the arrival of aftershocks.